Kansas State at Salina - Knudsen, Brett; Stewart, Bill (Kansas State University, 2009)
This presentation discusses some aspects of sustainability research at K-State at Salina. This lecture argues that horizontal axis wind turbines appropriate for use in the Salina campus. It expounds the reasons for using vertical axis wind turbines and solar panels as a workable option. The talk describes the best locations for sustainable energy devices on campus.
Keywords: Kansas State University--Salina. College of Technology.; Wind turbines; Solar panels; Sustainability